2012
DOI: 10.1111/j.1440-1754.2012.02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric trainee supervision: Management changes and perceived education value

Abstract: We observed little evidence of supervisors directly observing trainees and trainees learning professional behaviours. A review of supervisory practices to promote more effective learning is needed. Communicating to paediatricians the value their trainees place on their input could have a positive effect on their engagement in supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Paediatric trainees consistently rate this educational impact of supervision higher than the supervisors, shown by the mixed methods study conducted by Van den Boom et al. [ 17 ], a methodological approach rarely employed in supervisory research. Using structured observations and a survey, this study’s conclusion was of the importance of consultants being aware of how trainees valued their input, since consultants often underestimate the significance of supervision to trainees.…”
Section: Introductionmentioning
confidence: 99%
“…Paediatric trainees consistently rate this educational impact of supervision higher than the supervisors, shown by the mixed methods study conducted by Van den Boom et al. [ 17 ], a methodological approach rarely employed in supervisory research. Using structured observations and a survey, this study’s conclusion was of the importance of consultants being aware of how trainees valued their input, since consultants often underestimate the significance of supervision to trainees.…”
Section: Introductionmentioning
confidence: 99%
“…Trainees and students at all levels of medical education report a scarcity of feedback from educational supervisors derived from directly observed performance . A recent study of paediatric trainees in New Zealand confirmed the rarity of direct observation . Norcini and Burch state that this ‘lack of assessment and feedback, based on observation of performance in the workplace, is one of the most serious deficiencies in current medical education practice’ (2007: 857) .…”
Section: Training and Assessment In Dbp – Evolutionary Goalsmentioning
confidence: 99%
“…There is a wealth of evidence supporting the efficacy (and effect size) of feedback on changing clinical performance . The benefit of regular, direct observation by supervisors on the acquisition of clinical competence and delivery of clinical care has been demonstrated . A training culture in DBP that ensures adequate direct observation of trainees is both a worthy and necessary aspiration.…”
Section: Training and Assessment In Dbp – Evolutionary Goalsmentioning
confidence: 99%